The Influence of Employee Involvement and Perceived Usefulness of CSR Programs on Employee Retention with the Mediation of Work Meaning - Endah Susilowati; Damelia Basauli Tambunan; Romauli Nainggolan (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to analyze the influence of employee engagement and perceived program usefulness on employee retention with the meaning of work as a mediating variable in the implementation of the digital-based CSR program Sedekah Sampah (Trash Charity) at PT Indocement Tunggal Prakarsa Tbk. The CSR program is part of the company's sustainability strategy that is not only oriented towards environmental impacts but also designed to increase active employee participation through the process of internalizing company values. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis method. The research data were obtained from 169 respondents who met the criteria as active participants of the Sedekah Sampah program. The results show that employee engagement and perceived program usefulness have a positive effect on the meaning of work and employee retention, both directly and indirectly through the meaning of work as a mediating variable. These findings indicate that participatory CSR not only contributes to the formation of the company's external image but also has significant implications for employee work attitudes and loyalty. Theoretically, this study strengthens the role of the meaning of work within the CSR framework, while practically provides managerial recommendations for designing sustainability programs that position employees as important actors in achieving company goals.